The Potential Geographical Indications in Pakistan (Journal of Social Sciences Review, 2023)
Geographical Indications (GI) are signs or tags that are used on agricultural, manufactured and natural goods in order to distinguish and protect them. The protection of such GI’s gives owners and cultivators due recognition in the world, and the buyers become aware of the original product belonging to a specific area. Pakistan enacted its GI law in 2020, and despite great potential, there have still been a very minute number of GI registrations. Pakistan is a diverse country rich in culture, values, and identities. There are numerous potential Geographical indications that have not been registered in the country due to various impediments in the processes of its registration. In order to register Geographical Indications in Pakistan, there are several barriers that must be overcome, including lack of knowledge, lack of technology, lack of a connection between IP tribunals and the business community, a dearth of subject-matter specialists, etc. Pakistani gemstones, fruits, delicacies, footwear, sports products, cutlery, sweets, traditional outfits and headgear are thought to be registered as strong GI's in the nation. These potential Geographical Indications, if registered, could earn a great amount of money for the national exchequer and improve the dilapidated financial condition of the country.
Keywords: Geographical Indications; Intellectual Property; Pakistan; Geographical Indications Registration and Protection Act 2020; Intellectual Property Organisation Pakistan